Visual Storytelling on The @Infosvipb Instagram Account as A Social Bridge for Digital Communication and Media Students - Gusti Kayleen Nicole; Wahyu Budi Priatna; Rici Tri Harpin Pranata; Sutisna Riyanto (Jurnal Indonesia Sosial Sains, 2025)
Visual storytelling is a method of conveying messages through structured visuals elements that enhance audience engagement. Instagram's @infosvipb account is widely used by IPB Vocational School students to share information, educational content, campus promotions, and cross-program interactions. This study examines the relationship between visuals storytelling on @infosvipb and its role US a social bridge for Digital Communication and Media students. Using a quantitative approach, questionnaires were distributed to 77 respondents. The findings show a significant positive relationship between visual storytelling and the formation of social bridges among students, particularly through reels, vocational-themed memes, and collaborative content.